2014
DOI: 10.1016/j.lisr.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A joker in the class: Teenage readers' attitudes and preferences to reading on different devices

Abstract: a b s t r a c t a r t i c l e i n f oAvailable online xxxx A comparison of 10th graders' reading of a narrative, literary text on a Sony e-reader and in print showed that preferences for reading devices are related to gender and to general reading habits. One hundred forty-three students participated in the study. In a school setting, students were asked to begin reading a novel on one device and then continue reading the same novel on the other device. A survey was administered before and after the reading se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 31 publications
2
29
2
4
Order By: Relevance
“…The study found that "only 7.98% of the students agreed with the statement 'if given a choice between an electronic or print version of a particular book, I would choose the electronic version, whereas around 50% disagreed with this statement" [39]. concerning their reading experience both in print and in digital form" [40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that "only 7.98% of the students agreed with the statement 'if given a choice between an electronic or print version of a particular book, I would choose the electronic version, whereas around 50% disagreed with this statement" [39]. concerning their reading experience both in print and in digital form" [40].…”
Section: Resultsmentioning
confidence: 99%
“…"Devoted readers" (students who read more than 5 books per month) were more likely to prefer reading paper books (5 out of 7). In the remainder of respondents, eBooks were preferred, with 56% of students reading 1-3 books per month preferring eReaders and 83% of students "who do not read in their leisure time" preferring eReaders [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reluctant readers may actually prefer to read digital books, because digital reading provides the opportunity to read easy books without their peers noticing (Miranda, Williams-Rossi, Johnson, & McKenzie, 2011). Digital reading may even attract reluctant readers who have had negative experiences with traditional reading materials (Tveit & Mangen, 2014).…”
Section: Media Comparisons Digital Versus Print Readingmentioning
confidence: 99%
“…A experiência de leitura em um computador não é necessariamente a mesma que em um tablet, assim como, não é igual ler um e-reader ou ler em um smartphone. Por esta razão, dentro do âmbito da pesquisa sobre a leitura, existem diferentes experimentos que buscam compreender qual é o impacto que o uso de cada um destes dispositivos pode gerar no processo e na prática da leitura (Dantas, 2017;Grzeschik, Kruppa, Marti, & Donner, 2011;Kang & Eune, 2012;Mangen, 2008;Richardson Jr & Mahmood, 2012;Tveit & Mangen, 2014). Igualmente, em virtude das diferentes opções e da importância que podem representar cada uma delas, nos últimos anos começa a aumentar o interesse por parte dos pesquisadores em realizar experiências enfocadas na observação da prática da leitura a partir do uso de diferentes sowares,e mais especificamente de aplicativos móveis utilizados para a leitura (Aamri, Greuter, & Walz, 2015;Li & Wu, 2017), como é o caso da pesquisa apresentada neste artigo.…”
Section: Introductionunclassified